The research articles on palm leaf manuscripts in Sri Lanka : a bibliomertic study using Google Scholar articles published during 2015-2022 - Kumara, H. U. C. S; Nishanthi, H. D. M.; Chandani, J.G.; Konpola, K.W.A.M. (Sri Lanka Library Association ; Colombo, 2024)
Palm leaf manuscripts are one of the oldest written forms found in Sri Lanka. Palm leaf manuscripts can be found throughout Sri Lanka in temples, monasteries, national museums, national archives, national libraries, university libraries, and special libraries. Bibliometric analysis is the application of statistical and mathematical tools to books and media communication. The statistical analysis of written publications, such as books, articles, or other publications, is known as bibliometric analysis. In the field of library and information science, as well as in other fields, library statistics are often used to provide quantitative analysis of academic research. This bibliometric study focuses on the research articles based on palm leaf manuscripts in Sri Lanka. The objectives of the study were to identify the annual growth of research publications, examine authorship patterns, and identify the most cited articles in palm leaf manuscripts in Sri Lanka during 2015-2022. Additionally, this study was used to identify the affiliation with the highest number of publications on palm leaf manuscripts in Sri Lanka and to analyze the most popular keywords in the publications. The study examined 36 research articles based on Sri Lankan palm leaf manuscriptsthat were published in Google Scholar between 2015 and 2022 and used bibliometric methodology to analyze the data. The Google Scholar advanced searching techniques were used to obtain data from Google Scholar with keywords including “palm leaf manuscript," “Sri Lanka,” “Ola leaf manuscript,'1 and “Sri Lanka." VOS viewer software and the Excel package were used to analyze and visualize the data in the study.According to the visualization data, the highest number of articles was published in 2016, 2017, 2019 and 2021, with 6 (17%) each. Most of the research in this field was carried out by individual authors. Of these, 19 (53%) were published by individual authors and 17 (47%) with co-authors. The results of this study have shown that “Sri Lanka” (30) and “Palm Leaf Manuscript” (33) are the strongest keywords of general link strength. Padmasiri G. R. was the author who the highest citations (12 citations) in his publication had titled “Management of indigenous knowledge in Sri Lanka, with special reference to indigenous medicine”. The most significant affiliation was the University of Kelaniya, which had the highest number of publications.
Keywords: Bibliometric Analysis, Palm leaf manuscripts, Ola leaf manuscripts, Google Scholar, VOSviewer